A New Age of SAR: How Can Commercial Smallsat Constellations Contribute to NASA's Surface Deformation and Change Mission? - Huang, Stacey A.; Osmanoğlu, Batuhan; Scheuchl, Bernd; Oveisgharan, Shadi; Sauber, Jeanne M.; Jo, MinJeong; Khazendar, Ala; Tymofyeyeva, Ekaterina; Wusk, Betsy; Albayrak, Arif (Earth and space science (Hoboken, N.J.), 2025)
In response to the 2017 Decadal Survey, NASA conducted a five‐year study on the Surface Deformation and Change (SDC) designated observable to study potential mission concepts. As part of the SDC mission study, the Commercial Synthetic Aperture Radar (ComSAR) subgroup was tasked with evaluating the current landscape of the SAR and interferometric SAR (InSAR) industry to assess whether NASA could leverage commercial smallsat products to meet the needs of the SDC science mission. The assessment found that although the commercial SAR industry is growing rapidly, off‐the‐shelf products can currently only make a small—albeit distinct—contribution to SDC mission goals. This gap is due to different design goals between current commercial systems (which prioritize targeted high‐resolution, non‐interferometric observations at short wavelengths with a daily or faster revisit) and a future SDC architecture (which focuses on broad, moderate‐resolution, and interferometric observations at long wavelengths). Even by 2030, planned commercial constellations are expected to only cover ∼ ${\sim} $65% of the area needed to match NISAR coverage. Still, high‐resolution and rapid‐repeat capabilities can augment scientific findings from a future SDC mission, as demonstrated by recent contributions from commercial data to applied sciences, cryosphere, and volcanology. Future innovations on smallsat constellation concepts could further contribute to SDC science and applications. Although current constellation designs are not fully able to satisfy desired SDC science capabilities, initial positive feedback to a request for information indicates a potential future path for a customized SDC commercial architecture; more studies will be needed to determine the feasibility of these approaches. Plain Language Summary The Surface Deformation and Change (SDC) mission was identified as one of the five Earth observatories based on the findings of the 2017 Decadal Survey. Characterizing and understanding surface motion and change is critical for studying a variety of Earth processes from earthquakes, volcanoes, and landslides and associated hazard forecasts and disaster managements to glacier dynamics, groundwater, sea level rise, and landscape change. To achieve these aims, precise radar instruments with precise orbit control and knowledge that are capable of observing all land and ice covered surfaces of the Earth are required. Due to the recent rapid growth in the commercial SAR industry, we assessed the current state of the industry to better understand how NASA could potentially leverage commercial smallsat products to meet the needs of the SDC science mission. We have found that current commercial offerings make a small, but significant, contribution to SDC mission goals and have unique science capabilities. However, even by 2030, planned commercial constellations are expected to cover only ∼ ${\sim} $65% of the area needed to match NISAR coverage. Future innovations on smallsat constellation concepts and a demonstrated market need from NASA could potentially increase the role of commercial SAR for science and applications. Key Points The science goals of NASA's Surface Deformation and Change (SDC) mission require capabilities not currently offered by commercial smallsat SAR data Commercial SAR smallsats do provide unique science contributions that augment SDC goals with high‐resolution and rapid repeat observations NASA's need for global coverage at longer wavelengths is not met by current market demand but could be provided by future commercial data